Rancang Bangun Sistem Informasi Pada Organisasi Perhimpunan Mahasiswa Katolik Republik Indonesia (PMKRI) Cabang Palopo Berbasis Web - Risma Risma; Aprianto Aprianto; Solmin Paembonan (Journal of Information System Research (JOSH), 2020)
The purpose of this study is to design and build an information system at the Indonesian Catholic Student Association of the Republic of Indonesia (PMKRI) Palopo Branch which is expected to be able to help and inform the time used and facilitate the delivery of information. This type of research is a prototype. The results of research in the form of a website consisting of several pages contain PMKRI profiles, albums and poto galleries of PMKRI activities, information, contacts and registration forms for new members, all of which have been functionally tested using the black box testing method. So with the application that has been built, it is expected to improve the performance of an institution / agency / company, especially at the Palopo Branch PMKRI.